1999
DOI: 10.1136/bmj.319.7216.1040
|View full text |Cite
|
Sign up to set email alerts
|

Is Helicobacter pylori associated with non-ulcer dyspepsia and will eradication improve symptoms? A meta-analysis

Abstract: Objectives To examine the association between Helicobacter pylori infection and non-ulcer dyspepsia, and to assess the effect of eradicating H pylori on dyspeptic symptoms in patients with non-ulcer dyspepsia. Design Systematic review and meta-analysis of (a) observational studies examining the association between Helicobacter pylori infection and non-ulcer dyspepsia (association studies), and (b) therapeutic trials examining the association between eradication of H pylori and dyspeptic symptoms in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
85
1
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(104 citation statements)
references
References 31 publications
5
85
1
6
Order By: Relevance
“…The present systematic review of studies on H pylori and dyspepsia involves more than 3 times as many patients in observational studies (9818 vs 2764 patients) and almost 3 times as many in randomized trials of H pylori eradication (2340 vs 778 patients) as were in a 1999 update 88 of previous reviews. 10,11 Moreover, whereas these previous reviews inappropriately combined results from substantially different observational studies (eg, those involving different diseases and/or different study designs) and results from substantially different trials (eg, those with brief vs prolonged follow-up), the present review avoids such potential biases and the misleading claims that may arise from them.…”
Section: Commentmentioning
confidence: 99%
“…The present systematic review of studies on H pylori and dyspepsia involves more than 3 times as many patients in observational studies (9818 vs 2764 patients) and almost 3 times as many in randomized trials of H pylori eradication (2340 vs 778 patients) as were in a 1999 update 88 of previous reviews. 10,11 Moreover, whereas these previous reviews inappropriately combined results from substantially different observational studies (eg, those involving different diseases and/or different study designs) and results from substantially different trials (eg, those with brief vs prolonged follow-up), the present review avoids such potential biases and the misleading claims that may arise from them.…”
Section: Commentmentioning
confidence: 99%
“…A metaanalysis of a large number of controlled studies indicated that the presence of Hp gastritis in the absence of peptic ulcer may be a risk factor in non-ulcer dyspepsia (odds ratio 1.6, IC(95%) = 1.4-1.8) and symptoms improve when the organism is successfully eradicated (1.9, IC(95%) = 1.3-2.6) (10) . In children a positive correlation between Hp gastritis without peptic ulcer and dyspeptic symptoms or recurrent abdominal pain (17) has not been well established (8,14,22) .…”
mentioning
confidence: 99%
“…Two systematic reviews have provided conflicting results regarding the effect of H. pylori eradication on symptom resolution in patients with non-ulcer dyspepsia (2,3). These reviews, however, have been criticized on methodological grounds.…”
mentioning
confidence: 99%
“…Non-ulcer dyspepsia is defined as persistent or recurrent upper abdominal discomfort, of at least 12 weeks duration, with no evidence of organic disease on investigation. The prevalence of non-ulcer dyspepsia in adults is around 10% and H. pylori infection is slightly more prevalent in adults with non-ulcer dyspepsia compared with healthy controls (2).…”
mentioning
confidence: 99%